Dishevelled-Associated Activator of Morphogenesis 2 (DAAM2) Predicts the Immuno-Hot Phenotype in Pancreatic Adenocarcinoma - Zhang, Qinglin; Pan, Jiadong; Nie, He; Wang, Hui; An, Fangmei; Zhan, Qiang (Frontiers in Molecular Biosciences, 2022)
Background: DAAM2 participates in the oncogenesis and progression of human cancers. Although the role of DAAM2 in cancers has been preliminarily investigated, its correlations with antitumor immunity are unclear. Methods: A pancancer analysis was conducted to explore the immunological role of DAAM2 based on RNA sequencing (RNA-seq) data downloaded from The Cancer Genome Atlas (TCGA). Next, correlations between DAAM2 and immunological characteristics in the tumor microenvironment (TME) of pancreatic adenocarcinoma (PAAD) were evaluated. In addition, the role of DAAM2 in predicting the clinical characteristics and the response to various therapies in PAAD were also assessed. In addition, the correlations between DAAM2 and the emerging immunobiomarker N6-methyladenosine (m6A) genes were also evaluated. Results: Pancancer analysis revealed that DAAM2 exhibited positive correlations with a majority of immunomodulators, tumor-infiltrating immune cells (TIICs) and inhibitory immune checkpoints in several cancer types, including PAAD. In addition, DAAM2 was associated with an inflamed phenotype in the TME. DAAM2 also predicted significantly higher responses to chemotherapy, anti-EGFR therapy and immunotherapy but lower responses to anti-ERBB2 and antiangiogenic therapy. In addition, DAAM2 was correlated with immune-related microbiota. Conclusions: In PAAD, DAAM2 is associated with an immuno-hot phenotype and can help predict the outcome of various therapeutic options. Overall, DAAM2 is a promising indicator for assessing high immunogenicity in PAAD.